Photo-oxidation of water sensitized by TiO2 and WO3 in presence of different electron acceptors - A. Mills (Revista Mexicana de Física, 2004)
The photo-oxidation of water is studied in presence of UV-light (¸ < 400 nm) using titanium dioxide (TiO2) and tungsten oxide (WO3;microandnano-crystalline) semiconductors in presence of different sacrificial electron acceptors (SEA): Fe(NO3)2, Na2S2O8, Ce(SO4)2,Co[(NH3)5Cl]Cl2, AgNO3, HgCl2 and Cu(NO3)2. TiO2 is 5 to 10 times more photoactive than WO3 with reference to oxygen evolution.Ag ions are the best of the SEAs, for all the semiconductors tested in the photo-redox process. No oxygen evolution is observed whenHg2+ or Cu2+ ions are used as SEAs. The effect of high (10-2 mol dm-3) and low (10-3 mol dm-3) SEA concentrations is also studied but no common trend is observed. Instead, each system (i.e., SEA+H2O+Semiconductor) exhibits a different behaviour and the results arerationalised in terms of the spectral and redox potential features of the system.